MALAM bencana 1965 dalam belitan krisis nasional / Editor, Taufik Abdullah, Sukti Abdurrachman, dan Restu Gunawan - SUKRI Abdurrachman; RESTU Gunawan; TAUFIK Abdullah (Yayasan Pustaka Obor Indonesia, 2013)
xxxiv, 472 hlm, ; 24 cm.